Evolution and development of the olfactory neurons in the olfactores clade - Poncelet, G (2021)
In vertebrates, specialised olfactory systems and associated neurons are crucial to sense the outside chemical world. They also play a notable part in reproduction with the role of GnRH-producing neurons, derived from the olfactory placode, in sexual maturation and fertility. Despite the vital importance of these olfactory cell types, our knowledge of their evolutionary origin remains limited. In this work, a comparative approach is undertaken to study the development of olfactory neurons and provide insights into their evolutionary history. Two main organisms are used for comparison: the lamprey Lampetra planeri and the ascidian Ciona intestinalis. These model species are used to investigate the expression, regulation, and function of specific genes to trace olfactory cell type relationships across vertebrates and their chordate relatives. First, the embryonic origin and specification of hypothalamic GnRH secretory neurons in lamprey is examined to develop a pan-vertebrate view of the origin and specification of these crucial neurosecretory cells. The potential association during embryogenesis with the developing olfactory system is investigated and this study provides support for the hypothesis that lamprey hypothalamic GnRH cells do not derive from the nasal placode, despite some specification mechanisms appearing conserved with olfactory-derived GnRH neurons of jawed vertebrates. Second, it is revealed that the palp axial columnar cells (ACCs) of Ciona have homologies with olfactory sensory and secretory neurons of vertebrates. The regulation, expression, and function of MS4A and GnRH genes in the palp ACCs, combined with data from vertebrates, suggest a common evolutionary origin at cell-type level to explain how the olfactory-derived cell types in vertebrates derived from an ACC-like GnRH/chemosensory multifunctional precursor by segregation of functions. Finally, a microfluidic chip for immobilisation and controlled stimulation of Ciona larvae is designed and built to interrogate whether the larva responds to chemical stimuli. The detection by live cell calcium imaging of a CO2-evoked response upon chemical stimulation represents the first experimental evidence that ascidian larva sense chemical cues in their environment and provides a valuable tool for further investigations.